The possibility of using serum and salivary alkaline/acidic Ribonuclease as potential biomarkers for ductal carcinoma in situ detection among Iraqi patients - Jabbar, Samar Ahmed; Hasan, Hathama Razooki; El Abdeen, Atheer Abd elqader Zain (Iraqi Journal of Science, 2026)
Ribonucleases (RNases) play a crucial role in various biological processes. Many studies have affirmed their significant role in numerous types of cancer. Saliva is an absorbing fluid that has attracted the attention of researchers due to its essential role in pathological and physiological situations. Therefore, this study aims to explore the relevance of alkaline and acidic Ribonuclease activities in serum and saliva for the diagnosis of breast tumours as well as the potential of using saliva as an alternative diagnostic fluid for ductal carcinoma in situ (DCIS) patients and benign tumour. The study examined changes in RNase activities in the serum and saliva of some breast-tuomr patients. The result demonstrated a significant elevation (P<0.0001) in alkaline and acidic RNase activities and specific activities of ductal carcinoma in situ patients group in both fluids in addition to a significant correlation between serum and saliva in alkaline RNase activity of the ductal carcinoma in situ patients group (P<0.002). These findings suggest that alkaline RNase activity could be used as an alarm and prediction tool for ductal carcinoma in situ disease.